Pengaruh Customer Relationship Marketing dan Kualitas Layanan Terhadap Kepuasan Nasabah - Tsaratullah Azhari; Mariko, Suhatri; Laila, Yulia (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa, 2023)
This research aims to determine the influence of Customer Relationship Marketing and Service Quality on Customer Satisfaction at PT.BPRS Carana Kiat Andalas. The method used in this research is a quantitative approach using SPSS version 25. Sampling was carried out using the Purpose Sampling technique and used 100 respondents as samples. The primary data in this study were questionnaires distributed to respondents via the google form, interviews with the bank, and observation. While secondary data collection of data from publication repost, books, research journals, articles and library research . The data analysis methods used are validity testing, reliability testing, classical assumption testing, multiple linear regression analysis and hypothesis testing. The research results show that Customer relationship Marketing (X1 influences Customer Satisfaction with a t count value of 3,240 and Service Quality (X2) influences Customer Satisfaction with a t count value of 18,024. Meanwhile, Customer relationshionship marketing (X1), Service Quality (X2)simultaneously have a significant effect on customer satisfaction at PT.BPRS Carana Kiat Andalas with an F Count value of 252,906. Throught the adjust R square value, it is also known that the Customer Relationship Marketing and Service Quality variables contribute 83,6% to customer satisfaction. While the remaining 16,4% is influenced by other variables. Keywords: Customer Relations hip Marketing,Service Quality, Customer satisfaction.